2022
DOI: 10.1590/1980-220x-reeusp-2022-0115en
|View full text |Cite
|
Sign up to set email alerts
|

Assessment tools for elder abuse: scoping review

Abstract: Objective: to map assessment tools for elder abuse and determine the psychometric properties of each one. Method: scoping review developed according to recommendations of the JBI Institute Reviewer’s Manual in databases and gray literature. Results: seventeen tools were identified for measuring situations of elder abuse. They were categorized into 1) Tools for assessment of risk for abuse, and 2) Tools for identification of abuse. According to risk for abuse, Vulnerability to Abuse Screening Scale was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, this study showed psychometric limitation since the internal structure of the 17 scales examined was not evaluated by validity evidences. 35 The interRAI-HC recognises that it is ‘…difficult to assess the extent of financial abuse in the absence of detailed information on financial resources… and that not all economic trade-offs are due to abuse…’. 36 Finally, the interRAI-HC assessment was not designed to capture EA and indeed lacks sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study showed psychometric limitation since the internal structure of the 17 scales examined was not evaluated by validity evidences. 35 The interRAI-HC recognises that it is ‘…difficult to assess the extent of financial abuse in the absence of detailed information on financial resources… and that not all economic trade-offs are due to abuse…’. 36 Finally, the interRAI-HC assessment was not designed to capture EA and indeed lacks sensitivity.…”
Section: Discussionmentioning
confidence: 99%